2017
DOI: 10.1097/md.0000000000005902
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective observational study comparing the international hip dysplasia institute classification with the Tonnis classification of developmental dysplasia of the hip

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 15 publications
5
43
0
5
Order By: Relevance
“…Moreover, the ossi c nucleus was not present in 34% hips. Comparing IHDI classi cation to Tönnis classi cation, Both Miao and Brandon et al [13,14] concluded that IHDI classi cation is more exibly and better re ect the severity of the condition, especially for those cases without ossi c nucleus of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ossi c nucleus was not present in 34% hips. Comparing IHDI classi cation to Tönnis classi cation, Both Miao and Brandon et al [13,14] concluded that IHDI classi cation is more exibly and better re ect the severity of the condition, especially for those cases without ossi c nucleus of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…The IHDI classification, continuity of Shenton's line, AI, ossific nucleus center edge angle (ONCEA), and signs of AVN were evaluated in the final follow-up [15][16][17]. AVN also was classified in accordance with Kalamchi-MacEwen classification [18].…”
Section: Radiological Assessmentmentioning
confidence: 99%
“…The IHDI classification, continuity of Shenton's line, AI, ossific nucleus center edge angle (ONCEA), and signs of AVN were evaluated in the final follow-up. [15][16][17] AVN was also classified in accordance with Kalamchi-MacEwen classification. [18] Hips in which the Shenton arc was continuous and the CE angle was 15º or greater were considered to be centered.…”
Section: Radiological Assessmentmentioning
confidence: 99%